JANAZAH IN ISLAM, ITS APPLICATION AND PRACTICE BY MUSLIMS IN KATSINA STATE, NIGERIA - abdullahi, Maryam aminu; Yahaya, Atiku Graba (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2021)
Islam is an all-encompassing religion that provides Muslims with Divine guidance in all spheres of life. However, in Katsina, a predominantly Muslim society, there are emerging innovations associated with funeral rites (janāzah) and mourning of the dead. Such innovations include, among others, competitions among mourners, discriminatory treatment among the mourners, and sniffing and rubbing the head (especially by elderly women) with the textile material that was used in accompanying the corpse to the grave. These innovations contradict the teachings of Islam on funeral rites and mourning. This paper, therefore, investigates the issues, analyzes them and proffer solutions from Islamic perspective. The paper used library and fieldwork methods. In the former, it widely consults relevant works in studying the teachings of Islam on the concept of janāzah. As for the latter, interview was conducted with relevant informants, and information related to origin, nature and effects of the innovations on the life of the Muslims in the study area were obtained. The paper finally emphasizes on the importance of the Islamic teachings on the practice of janāzah and suggested ways to eradicate the innovations associated with death, funeral rite and mourning in the study area. The paper found out that innovations introduced into practice of janāzah by Muslims in Katsina state have affected them religiously, socially and economically. It is concluded that Muslims need to abide by the true teachings of Islam in all aspects of life.